Affidavit for Viktor and Marianne Homburger by Ludwig Bendix - Bendix, Ludwig (1940)
Ludwig Bendix (1877-1954), New York investment banker and colleague of Viktor Homburger (1888-1968), writes an affidavit for Homburger and his wife, Marianne Homburger (1903-1986), who are interned at the Gurs Concentration Camp in Southern France. Bendix vouches for the Homburgers' good character in order to obtain an immigration visa for the couple.
Keywords: Bendix, Ludwig, 1877-1954; Affidavits; Homburger, Marianne, 1903-1986; Homburger, Viktor, 1888-1968; Emigration and immigration